Standardizing the Concept of Lean: A Literature Review - Islam, A. S. M. Touhidul; Sorooshian, Shahryar; Syed Radzi, Rahamaddulla; Shariman, Mustafa (Academic Publications, 2018)
In modern day‟s global competition, companies adopting lean management to maximize productivity and quality with lower cost and time spent. But the success rate of lean implementation is far below than assumed. The authors noticed that there is a scope to research onunderstanding lean by definitions. Fundamentally, the term “Lean”, mostly representing the Toyota production system has been being defined by many authors in many forms. But still the uniformity and clarity is not gained to come to a conclusion with consensus. Hence thispaper aims to eliminate variability in defining lean bycreatinga versatile, easily understandable and acceptable meaningby reviewing contemporary literature and interviewing industry experts.